Effects of Drying Temperature on Physicochemical Properties, Bioactive Compounds, Antioxidant, and Antibacterial Activities of Three Sweet Potato Cultivars - CheeKham, Phuriwat; Uprarawanna, Utsaphong; Rochanasak, Sirikorn (Journal of Food Health and Bioenvironmental Science, 2024)
This study investigates the impact of drying temperature (60-100°C) on the physicochemical properties, bioactive compounds, antioxidant, and antibacterial activities of three sweet potato cultivars: yellow (HRDI Sp-74), orange (HRDI Sp-72), and purple (HRDI Sp-61). Using a completely randomized design, the results revealed that while drying temperature did not affect yields, it reduced the lightness (L*) of the cultivars. Among them, HRDI Sp-61 exhibited the highest protein content (6.35 g/100g, p ≤ 0.05), whereas HRDI Sp-72 showed the highest phenolic compound content (409.88 mg GAE/100 g powder), which was in line with DPPH antioxidant activity. All dried sweet potato extracts displayed antibacterial activity against Escherichia coli, with HRDI Sp-61 demonstrating the most significant inhibitory effects (10.50 and 10.07 mm zones of inhibition).